Exhaled Volatile Organic Compounds Identify Allergic Patients Among Individuals With Chronic Rhinitis - Sola-Martinez, Rosa Alba; Zubiaga-Fernandez, Laura; Figuerola, Marta; Cruz-Amaya, Anyith; Aranda, Carlos J.; Torres, Maria J.; Eguiluz-Gracia, Ibon; Rondon, Carmen; De Diego Puente, Teresa; Testera-Montes, Almudena (Wiley, 2026)
Background: The nasal allergen challenge (NAC) is the gold standard to diagnose allergic rhinitis (AR) and local allergic rhi- nitis (LAR), but its clinical use remains limited. We investigated whether volatile organic compounds (VOC) in exhaled breath could identify allergic individuals among patients with chronic rhinitis. Methods: Exhaled breath samples were collected before and 24 h after NAC in participants with AR, LAR, non-allergic rhinitis (NAR), and healthy control (HC). Samples were analyzed using gas chromatography–mass spectrometry, focusing on saturated hydrocarbons. Associations with fractional exhaled nitric oxide (FeNO) and blood eosinophils were also assessed. Results: We included 28 AR, 31 LAR, 29 NAR, and 14 HC individuals, divided into training and validation sets. A predictive model based on two VOCs (decane and nonadecane) discriminated allergic (AR + LAR) from non-allergic (NAR + HC) subjects (AUC 0.721, 95% CI: 0.506–0.936; permutation test p = 0.009), with moderate performance in the validation set (AUC 0.760, 95% CI: 0.585–0.935; 76.5% sensitivity, 69.2% specificity). Similarly, these two VOCs moderately differentiated LAR and NAR patients (AUC 0.737, 95% CI: 0.545–0.929; permutation test p = 0.011). At baseline, decane levels were higher in LAR than HC subjects (p = 0.007), nonadecane levels were higher in LAR than NAR individuals (p = 0.026), and decane, styrene, and nonanal levels were higher in patients with FeNO ≥ 25 ppb (all p ≤ 0.016). No associations were observed between VOCs and blood eosinophils. NAC induced a significant reduction in nonadecane in allergic patients (p = 0.012), but not in non-allergic subjects. Conclusion: Exhaled decane and nonadecane might serve as non-invasive biomarkers of allergic inflammation in rhinitis pa- tients, potentially supporting NAC indication. Elevated exhaled nonanal, decane, and styrene may reflect T2 airway inflamma- tion. These exploratory findings require validation in larger, multicenter cohorts with accuracy-improving potential.
Keywords: Fiebre del heno; Alergia; allergic rhinitis; breath analysis; decane; nonadecane; nonanal; styrene